ZBTB48 is both a vertebrate telomere‐binding protein and a transcriptional activator - Jahn, Arne; Buchholz, Frank (EMBO reports, 2017)
Telomeres constitute the ends of linear chromosomes and together with the shelterin complex form a structure essential for genome maintenance and stability. In addition to the constitutive binding of the shelterin complex, other direct, yet more transient interactions are mediated by the CST complex and HOT1/HMBOX1, while subtelomeric variant repeats are recognized by NR2C/F transcription factors. Recently, the Kruppel‐like zinc finger protein ZBTB48/HKR3/TZAP has been described as a novel telomere‐associated factor in the vertebrate lineage. Here, we show that ZBTB48 binds directly both to telomeric and to subtelomeric variant repeat sequences. ZBTB48 is found at telomeres of human cancer cells regardless of the mode of telomere maintenance and it acts as a negative regulator of telomere length. In addition to its telomeric function, we demonstrate through a combination of RNAseq, ChIPseq and expression proteomics experiments that ZBTB48 acts as a transcriptional activator on a small set of target genes, including mitochondrial fission process 1 (MTFP1). This discovery places ZBTB48 at the interface of telomere length regulation, transcriptional control and mitochondrial metabolism. See also: L Garcia‐Exposito & RJ O'Sullivan (June 2017). Synopsis The zinc finger protein ZBTB48 directly binds telomeres and limits their elongation. ZBTB48 also transcriptionally activates a defined set of genes, including mitochondrial fission process 1, linking telomere length regulation and mitochondrial metabolism. ZBTB48 is a novel direct telomere‐binding protein recognizing telomeres via its ZnF11 domain.Loss of ZBTB48 leads to longer telomeres, establishing ZBTB48 as a negative regulator of telomere length.ZBTB48 is a transcriptional activator controlling a defined set of target genes including mitochondrial fission process 1, MTFP1.Loss of ZBTB48‐dependent expression of MTFP1 phenocopies previously reported defects in the mitochondrial network